2019
DOI: 10.1039/c8ra08378a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and feasibility analysis of methyl ester of Sesbania seeds oil (MESSO) as alternate liquid dielectrics in distribution transformers

Abstract: Graphical presentation of the processing of methyl ester of Sesbania seeds oil (MESSO) as an alternative dielectric in transformers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Although there was some skepticism, as reported above, there were other publications that suggested the use of vegetable oils, since these presented a dielectric strength comparable to that of mineral oil and the saturated fatty acid content in such oils retarded the deterioration of the insulating fluid in hightemperature environments or long-term storage conditions. Moreover, vegetable oils showed more cooling ability and high insulation capacity than mineral oil [50]. Authors in [51] agree with [50], reporting that while oxidation of mineral oil produces sludge precipitates, vegetable oils are much more resistant to oxidation.…”
Section: Possible Alternatives To Transformer Oimentioning
confidence: 77%
See 1 more Smart Citation
“…Although there was some skepticism, as reported above, there were other publications that suggested the use of vegetable oils, since these presented a dielectric strength comparable to that of mineral oil and the saturated fatty acid content in such oils retarded the deterioration of the insulating fluid in hightemperature environments or long-term storage conditions. Moreover, vegetable oils showed more cooling ability and high insulation capacity than mineral oil [50]. Authors in [51] agree with [50], reporting that while oxidation of mineral oil produces sludge precipitates, vegetable oils are much more resistant to oxidation.…”
Section: Possible Alternatives To Transformer Oimentioning
confidence: 77%
“…Moreover, vegetable oils showed more cooling ability and high insulation capacity than mineral oil [50]. Authors in [51] agree with [50], reporting that while oxidation of mineral oil produces sludge precipitates, vegetable oils are much more resistant to oxidation.…”
Section: Possible Alternatives To Transformer Oimentioning
confidence: 77%
“…Sesbania aculeate oil, Potassium hydroxide (KOH), and methanol (CH3OH) is taken as raw materials in the SAOME biodiesel production. Note that Sujitha et al [27] prepared methyl ester of sesbania seed oil (MESSO), an insulating fluid by transesterification process for transformers. They employed the transesterification process in which 1:6 ratios of sesbania oil and methanol, concentrated H2SO4 as catalysts are used to produce an insulating fluid with high thermal and oxidation stability.…”
Section: Methods and Materials Biodiesel Productionmentioning
confidence: 99%
“…The investigations conducted by Umal et al on Neem Oil Epoxy Methyl Esters showed that its dielectric losses are in the dielectric loss range of the bio-based insulating oils [10]. According to the work of Ravulapalli et al, the dielectric losses and the volume resistivity of Methyl Ester of Sesbania Seeds oil are higher than those of mineral oil [11].…”
Section: Mariprasath Et Al Found That the Breakdown Voltage Of The Imentioning
confidence: 99%